2015
DOI: 10.1021/acs.jpcb.5b03533
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Bonding and Chalcogen Bonding in 4,7-Dibromo-5,6-dinitro-2,1,3-benzothiadiazole

Abstract: An organic solid, 4,7-dibromo-5,6-dinitro-2,1,3-benzothiadiazole, has been designed to serve as an illustrative example to quantitatively evaluate the relative merits of halogen and chalcogen bonding in terms of charge density features. The compound displays two polymorphic modifications, one crystallizing in a non-centrosymmetric space group (Z' = 1) and the other in a centrosymmetric space group with two molecules in the asymmetric unit (Z' = 2). Topological analysis based on QTAIM clearly brings out the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 53 publications
5
23
0
Order By: Relevance
“…S5) show essential chemical features such as the anisotropic electron-density distribution around the Br atom. Furthermore, in accordance with previous reports of related experimental charge-density studies (Pavan et al, 2015), the presence of a charge-depleted region on the Br atom along the extension of the C-Br bond was clearly evident.…”
Section: Multipole Refinementsupporting
confidence: 92%
“…S5) show essential chemical features such as the anisotropic electron-density distribution around the Br atom. Furthermore, in accordance with previous reports of related experimental charge-density studies (Pavan et al, 2015), the presence of a charge-depleted region on the Br atom along the extension of the C-Br bond was clearly evident.…”
Section: Multipole Refinementsupporting
confidence: 92%
“…In each crystal shown in Figure , there are at least two Br ⋅⋅⋅ Br or I ⋅⋅⋅ I contacts for each monomer that are at or below the respective van der Waals radii sum of 3.70 Å for (Br+Br) and 3.96 Å for (I+I). We note that the addition of polarizing nitro groups tightens the XB interactions even further, as observed in 9 g , which now includes near linear Br ⋅⋅⋅ Br/N contacts at 3.47 and 3.06 Å, respectively. A new O ⋅⋅⋅ S donor–acceptor contact at 3.21 Å also emerges, which is below the sum of the van der Waal radii of (O+S)=3.32 Å.…”
Section: Resultssupporting
confidence: 53%
“…[110][111][112][113] In each crystal shown in Figure10, there are at least two Br···Br or I···Ic ontacts for each monomer that are at or below the respective van der Waals radii sum of 3.70 for (Br + Br) and 3.96 for (I + I). We note that the addition of polarizing nitro groups tightenst he XB interactions even further,a so bserved in 9g, [113] which now includes near linear Br···Br/N contacts at 3.47 and 3.06 ,r espectively.Anew O···Sd onor-acceptor contact at 3.21 also emerges,w hich is below the sum of the van derW aal radii of (O + S) = 3.32 . Fluorination:Distinct from the derivatives bearing higherhalogen substituents, highly aligneds quares are abundantf or most of the fluoro-benzothiadiazoles (5b, 7, 8, 9b-9e).…”
Section: The 2s-2n Squarec Lass Assembled By Chalcogen Bondingmentioning
confidence: 99%
“…[31] An early study of non-covalent interactions involving chalcogen atoms was reported for systems containing F 2 O, F 2 S and F 2 Se. [34] A large-scale computational study exploring the main features of chalcogen bonding for a series of donors (involving S, Se and Te atoms) complexed with halide ions and neutral Lewis bases (containing O, N and C atoms) was recently reported. [34] A large-scale computational study exploring the main features of chalcogen bonding for a series of donors (involving S, Se and Te atoms) complexed with halide ions and neutral Lewis bases (containing O, N and C atoms) was recently reported.…”
Section: Introductionmentioning
confidence: 99%